Improved equation to describe the induction motor currents during nearby three‐phase short‐circuits - Elmer Sorrentino; Andres Vera (IET Electric Power Applications)
Abstract This article shows an improved equation to describe the induction motor currents during a three‐phase short‐circuit near to motor terminals. The proposed equation considers three details which are not in the equation shown in the IEEE Std. 551: (a) the equivalent frequency of these currents is not strictly equal to the grid frequency; (b) the magnitude of the DC component is not strictly equal to the magnitude of the AC component; (c) an angle is included to consider the instant of fault occurrence. The proposed equation was verified by experimental results, which were also verified by simulations. It is shown that the equivalent frequency of analysed currents is not exactly the grid frequency due to the sudden change of the machine speed (caused by the high braking torque originated by high transient currents during the short‐circuit). This effect is larger in smaller motors. The AC and DC components of the analysed currents have their own time constants, which are usually estimated from motor equivalent circuit. The application of the improved equation was useful to demonstrate that such a procedure does not lead to accurate results in case of the DC time constants of small motors. Finally, an example illustrates a case that cannot be well described by the equation from the IEEE Std. 551, whereas the result from the proposed equation is very similar to the measured current.